2004
DOI: 10.1074/jbc.m309007200
|View full text |Cite
|
Sign up to set email alerts
|

Multivalent Mechanism of Membrane Insertion by the FYVE Domain

Abstract: Targeting of a wide variety of proteins to membranes involves specific recognition of phospholipid head groups and insertion into lipid bilayers. For example, proteins that contain FYVE domains are recruited to endosomes through interaction with phosphatidylinositol 3-phosphate (PtdIns(3)P). However, the structural mechanism of membrane docking and insertion by this domain remains unclear. Here, the depth and angle of micelle insertion and the lipid binding properties of the FYVE domain of early endosome antig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
109
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(118 citation statements)
references
References 51 publications
5
109
0
Order By: Relevance
“…The latter can be explained by the fact that the RFLR motif is present and may contribute to PtdIns ( for PtdIns(3)P to be 2.3 µM. This value is within the range of other PtdIns(3)P-binding protein domains such as the EEA1 FYVE and the Vam7p PX domains (131,132), but is 3-10-fold higher to that estimated for Avr1b and AvrL567 using effector binding to cells and liposome binding assays (11); this higher affinity value may be explained by the presence of additional tags in the proteins tested in these assays that may contribute to the binding (134). Nonetheless, a modest affinity of a protein to phosphoinositides, such as Avh5, may be required for its further release from intracellular membranes to target other subcellular compartments (135).…”
Section: Discussionmentioning
confidence: 55%
“…The latter can be explained by the fact that the RFLR motif is present and may contribute to PtdIns ( for PtdIns(3)P to be 2.3 µM. This value is within the range of other PtdIns(3)P-binding protein domains such as the EEA1 FYVE and the Vam7p PX domains (131,132), but is 3-10-fold higher to that estimated for Avr1b and AvrL567 using effector binding to cells and liposome binding assays (11); this higher affinity value may be explained by the presence of additional tags in the proteins tested in these assays that may contribute to the binding (134). Nonetheless, a modest affinity of a protein to phosphoinositides, such as Avh5, may be required for its further release from intracellular membranes to target other subcellular compartments (135).…”
Section: Discussionmentioning
confidence: 55%
“…However, additional anionic phospholipids also participate in targeting FYVE domain-containing proteins (33). To determine whether the ESCRT-0 complex can also bind to membranes that are devoid of PI3P, we conducted a series of liposome coflotation assays.…”
Section: The Fei Adaptor Complex Regulates Protein Sorting In the Endmentioning
confidence: 99%
“…Structural and biophysical studies have indicated that several factors beside PtdIns(3)P binding contribute to the membrane affinity of FYVE domains. They include nonspecific electrostatic interactions between basic protein residues and the anionic membrane surface (27)(28)(29), hydrophobic interactions achieved by the partial membrane insertion of the residues located in the loop (so-called turret loop, see Fig. 1) near the PtdIns(3)P-binding pocket (24,25,27,29,30), and FYVE domain dimerization (21,25,26).…”
mentioning
confidence: 99%
“…They include nonspecific electrostatic interactions between basic protein residues and the anionic membrane surface (27-29), hydrophobic interactions achieved by the partial membrane insertion of the residues located in the loop (so-called turret loop, see Fig. 1) near the PtdIns(3)P-binding pocket (24,25,27,29,30), and FYVE domain dimerization (21,25,26). Mutational studies of many FYVE domain-containing proteins have indicated that FYVE domains play an important role in their binding to endosomes in the cell (21,31,32).…”
mentioning
confidence: 99%